ANALISIS DAMPAK INDIKATOR SOSIAL EKONOMI TERHADAP TINGKAT KRIMINALITAS PADA 13 KOTA BESAR DI INDONESIA TAHUN 2015-2021: Studi Pada 13 Kota Besar di Indonesia Tahun 2015-2021 - M. Ilham G Mubarok Mubarok; Tete Saepudin (Universitas Pasundan, 2023)
This research aims to determine the influence of socio-economic indicators on crime rates in 13 large cities in Indonesia in 2015-2021. This research is quantitative research using the path analysis method. The results of the study show that partially, GRDP per capita and the open unemployment rate have a positive and significant effect on the poverty rate. Population density and human development index variables have a negative and significant effect on the level of poverty. Simultaneously the variables GRDP per capita, population density, human development index, and open unemployment rate have a significant effect on the level of poverty. Partially the per capita GRDP variable has a negative and significant effect on the crime rate and the open unemployment rate variable has a positive and insignificant effect on the crime rate. The variables of population density, human development index, and poverty rate have a positive and significant effect on crime rates. Simultaneously the variables GRDP per capita, population density, human development index, open unemployment rate, and poverty rate have a significant effect on crime rates.